Dietary intake and nutritional practices of elite Greek aquatic athletes - Farajian, P.; Kavouras, S. A.; Yannakoulia, M.; Sidossis, L. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
To investigate whether aquatic athletes follow optimal dietary intake, 58 athletes, all members of the Greek national swimming and water polo teams, were tested. Dietary intake was assessed at the nutrient, food, and food group level using the 24-h recall method and a food frequency questionnaire. Mean energy intake for males and females was 14.3 and 8.5 MJ, respectively. Mean carbohydrate consumption for male and female athletes was 4.5 g/kg and 3.8 g/kg of body weight, respectively. Fat intake was 153 g for males and 79 g for females. A significant number of the athletes (71% of the males, 93% of the females) did not meet the Dietary Reference Intakes for at least one of the antioxidant vitamins. The data suggest that athletes of both genders consumed too much fat and too little carbohydrate. Insufficient fruit and vegetable intake was related to low intake of antioxidants.